PROBLEMS OF DOCUMENT FLOW OF THE MODERN ENTITY - Elena Ponomareva; Malvina Gyulnezerova (Вестник Северо-Кавказского федерального университета)
In article the essence, a role and problems of document flow of the modern entity, and also questions of implementation of the electronic document management systems (EDMS) in educational institutions are considered. Development of EDMS, their transformation taking into account modern information technologies, relevance of application of an electronic document management system in activities of the modern organization are analyzed.